Legal Review Of Breach Of Land Dispute Over Land Sale And Purchase Between Land Owner And PT. Pancapuri Indoperkasa : Serang District Court Decision Number 123/PDT/2025/PN. SRG - Mutari Madhuri; M. Nassir Agustiawan; Mohammad Hifni; Najar Pratama; Muhamad Jahiri; Dani Darmawan (Yayasan pendidikan dzurriyatul Quran, 2025)
This study examines the legal implications of a breach of contract dispute between a landowner and PT. Pancapuri Indoperkasa, as ruled in Serang District Court Decision Number 123/Pdt/2025/PN.Srg. The research employs a normative juridical approach with a case study method to analyze the application of civil law. Data were obtained from the Supreme Court’s Case Tracking Information System (SIPP), relevant legislation, legal journals, and expert opinions, analyzed descriptively and qualitatively. The findings reveal that PT. Pancapuri Indoperkasa was proven to have defaulted by failing to fulfill payment obligations despite having received the land, which had been delivered more than two years earlier. The court rejected the company’s argument of force majeure due to internal delays in permits and funding changes, affirming that such business risks are the company’s responsibility. The judges confirmed that all elements of breach valid agreement, unfulfilled obligation, delay, loss, and causal relation were legally proven, reflecting the correct application of Articles 1244 1252 of the Civil Code. This decision illustrates the court’s progressive interpretation of pacta sunt servanda and good faith, ensuring protection for the weaker party and achieving substantive justice